Electromagnetic Torque Calculation and Transmission Characteristic of Drum-type Solid Magnetic Couplers - Yang Chaojun; Wang Jian; Hang Tian; Qi Yutang; Wang Ao (Jixie chuandong)
In order to study the calculation formula of the electromagnetic torque and the transmission characteristics of the drum-type solid magnetic coupler (DSMC), a DSMC with 4 poles was taken as the research object. The magnetic equivalent circuit model introducing the induced current was established, combining with the Ampere's loop law and the 3-D magnetic effect to analyze and calculate the electromagnetic torque. The magnetic field distribution and the induced current distribution of the coupler and the mechanical characteristic curve under different input speeds were obtained by using the finite element simulation software. By moving the conductor rotor axially and changing the relative position of the two rotors, the effects of different meshing lengths on the electromagnetic torque were obtained. Finally, a test platform was built to verify the electromagnetic torque results obtained by the theoretical calculation and the finite element simulation. The experimental results are basically consistent with the above results. The model provides guidance for the design and optimization of the DSMC.